Analysis of Factors Affecting The Demand of Broiler Chicken Meat In Binjai City - Ummi Hasunah Nasution; Edhy Mirwandhono; Ma'ruf Tafsin; Hasnudi .; Armyn Hakim Daulay (Jurnal Peternakan Integratif, 2019)
Consumption of broiler chicken meat increase year by year in line with publicawareness increased of animal products. The demand for broiler chicken meat in Binjai Cityshows a fluctuating increase that estimated by a number of factors that influence it.The purposeof this research was identify the factor of family’s dependent number (X1), educational level(X2), family income (X3), price of broiler chicken (X4), taste (X5), age of respondent (X6), andprice of substitution was egg (X7) to broiler chicken demand in Binjai City.The analysismethod used in this research was multiple linear regression analysis method by using SPSS22.0. Sampling technique with slovin method with the samples were100 consumers of broilerchicken meat. This research was conducted from October until November 2017.The results showed that value of determination (R2) was 0,704. Simultaneously, the variablesshowed that they gave significant effect (P<0,05) to the demand of broiler chicken meat.Partially, family’s dependent number, income, chicken meat’s prices and tastes had asignificant effect to the demand of broiler chickens while the educational level, age ofrespondents and the price of egg did not give significant effect on the demand of broilerchicken meat in Binjai City. The conclusion of this research showed that the taste was the mostsignificant (increase) variable to the demand of broiler chicken in Binjai City and thenfollowed by the family’s dependent number, price of broiler chicken meat and family income.Keywords: Demand, Broiler Chicken, Price, Binjai